Development and validation of Lenalidomide in human plasma by LC-MS/MS - Ranganathan, Premanand (Saudi J Biol Sci, 2019)
A highly sensitive and ultra-fast high performance liquid chromatography- tandem mass spectrometry (LC–MS/MS) assay is developed and validated for the quantification of Lenalidomide in human plasma. Lenalidomide is extracted from human plasma by Liquid- Liquid Extraction by Ethyl Acetate and analyzed using a reversed phase isocratic elution on a XTerra RP18, (4.6 × 50 mM, 5 µm) column. A 0.1% Formic acid: Methanol (10:90% v/v), is used as mobile phase and detection was performed by Triple quadrupole mass spectrometry LC-MS/MS using electrospray ionization in positive mode. Fluconazole is used as the internal standard. The lower limit of quantification is 9.999 ng/mL for Lenalidomide. The calibration curves are consistently accurate and precise over the concentration range of 9.999 to 1010.011 ng/mL in plasma for Lenalidomide. This novel LC–MS/MS method competes with all the regulatory requirements and shows satisfactory accuracy and precision and is sufficiently sensitive for the performance of pharmacokinetic and bioequivalence studies in humans.